Impact of adsorbate–substrate interaction on nanostructured thin films growth during low-pressure condensation - Dvornichenko, Alina V.; Kharchenko, Vasyl O.; Kharchenko, Dmitrii O. (Beilstein Journal of Nanotechnology, 2025)
We discuss effects of elastic adsorbate–substrate interactions in processes of nanostructuring of thin films during low-pressure condensation in the framework of theoretical approaches and numerical simulations. It will be shown that an increase in the elastic interaction strength induces first-order transitions and pattern formation. We simulate deposition on one- and multicomponent substrates with different strengths of adsorbate–substrate interactions. We will show that an increase in the strength of adsorbate–substrate interactions stimulates the formation of stable surface structures during deposition, which leads to an increase in its coverage and the formation of a smaller number of adsorbate islands of larger size. At elevated adsorption rates, an increase in adsorbate–substrate interactions results in the transformation of the surface morphology and the formation of percolating adsorbate structures. Deposition onto multicomponent substrates leads to the formation of a stationary surface morphology with an elevated number of adsorbate islands of smaller size, compared to one-component substrates. This study provides a deep insight into the peculiarities of nanostructured thin films’ growth in low-pressure systems with different adsorbate–substrate bonding.
Keywords: adsorbate–substrate interaction; adsorptive systems; numerical simulations; pattern formation